Diagnostic Errors in Wilms' Tumors: Learning From Our Mistakes - de Carvalho, Lucas Garschagen; Kobayashi, Thiago; Cypriano, Monica dos Santos; Caran, Eliana Maria Monteiro; Lederman, Henrique Manoel; Alves, Maria Teresa de Seixas; Abib, Simone de Campos Vieira (Frontiers in Pediatrics, 2021)
Aim: To analyze clinical characteristics and image findings in patients initially diagnosed with renal masses and treated on the SIOP 2001 protocol for Wilms tumor (WT) that eventually were diagnosed with different pathologies. Methods: We reviewed the preoperative symptoms, laboratory tests and images of patients that were initially treated as WT and proved to have other diagnosis. Data from these patients were compared to the last 10 patients with WT and the last 10 patients with neuroblastoma (NBL) treated at a single institution. Results: From June 2001 to December 2020 we treated 299 patients with NBL and 194 with WT. Five patients treated with preoperative chemotherapy for WT were post operatively diagnosed with NBL (one patient had bilateral renal masses) and one with multifocal xanthogranulomatous pyelonephritis. Three underwent nephrectomy, two biopsies only and one adrenalectomy due to intraoperative characteristics. Regarding clinical presentation, abdominal mass or swelling was very suggestive of WT (P = 0.011); pain, although very prevalent in the study group (67%), was not statistically significant, as well as intratumoral calcifications on computed tomography (CT) (67%). Urinary catecholamines were elevated in all patients mistreated for WT with the exception of the patient with pyelonephritis in which it was not collected. Conclusion: Some pathologies can be misdiagnosed as WT, especially when they present unspecified symptoms and dubious images. Diagnostic accuracy was of 98.1%, which highlights the quality of the multidisciplinary team. Abdominal mass or swelling is highly suggestive of WT, especially in the absence of intratumoral calcifications on CT. If possible, urinary catecholamines should be collected at presentation as they help in the differential diagnosis of NBL.